The influence of evolutional processes on structural-typological qualification of modern Ukrainian (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
The article deals with the problem of analytization synthetic Ukrainian.  The main idea of the article is that: the typological changes in Ukrainian are not single-purposeful “from synthesis to analyticity”. There changes are subordinate to analytizational and synthetizational tendencies but synthetizational is the main. The article is devoted to detail analysis of level classification and semantics and functions of case forms and prepositional case forms of nouns. Each of the indirect cases being firmly set in synthetical forming of the language under investigation is caused by the fact that the form models of these cases provide the expression of syntaxeme types correlating with the primary (basic) function of the particular case. At the morphological level, syntactical means of case forming are obligatory in terms of functional semantic aspect. The author treats prepositional case word combinations as manifestation of analytism. The phenomenon of functional stress of flexion-expressed case element within analytical models of syntaxemes, which often occurs in Ukrainian under research, proves that synthetical case forming takes place at the syntactical level as well. The general conclusion about stability of morphological synthesis in the system of substantival forming of Ukrainian under investigation is the result of the analysis. In the system of verb facilities of expression of grammems of impredicative categories almost fully remain the sphere of displays of synthesis in Ukrainian. Synthetic and analytical formmodel unite only in composition of paradigms of predicative categories. Activation of an analytical tendency depends on activity and possibilities synthetic facilities. If a synthetic tendency accompanies the semantic evolution of the morphological system, leaning on language resources and mechanisms, then an analytical tendency plays this evolution an auxiliary, compensative role, assisting filling of those compartements in paradigms of categories or paradigms of separate lexemes, synthetic forming does not spread on that. Thus, an analytical tendency finds out the action wherein there are free from synthetic forming positions. Consequently two evolutional-typology tendencies do not counteract each other, but fastened mainly after different spheres.
Keywords: structural typology; synthesis; analyticity; noun; verb; morphological paradigm; morphological category; forming